Implementation of Educational Policies in Overcoming Juvenile Delinquency - Deding Ishak (ijd-demos, 2022)
AbstractThe role of education in the moral development of students is very strategic because shaping the morale of practical students can only be done through education; in this case, school members (principals, teachers, employees, and students) have a significant role in the development of character values. And student morale. Therefore, as a manager and leader, the principal is responsible for translating and implementing educational policies to shape the nature and morals of students, in this case, minimizing juvenile delinquency. This study aims to analyze the implementation of educational policies in overcoming juvenile delinquency. This study uses a qualitative method with a descriptive type of research approach to document/text studies. The study results show that in realizing the successful implementation of educational policies to overcome juvenile delinquency, three things can be influenced: the logic used by a policy, the nature of the cooperation needed, and substantial human resources. Besides that, in the elaboration of implementation, it will be successful if it also pays attention to communication, resources, school residents' attitudes, and the prevailing bureaucratic structure.Keywords: Education Policy, Students, Juvenile Delinquency. AbstrakPeran pendidikan dalam pengembangan moral siswa sangat strategis karena pembentukan moral siswa praktis hanya dapat dilakukan melalui pendidikan; dalam hal ini warga sekolah (kepala sekolah, guru, karyawan, dan siswa) memiliki peran yang signifikan dalam pengembangan nilai-nilai karakter. Dan moral siswa. Oleh karena itu, sebagai manajer dan pemimpin, kepala sekolah bertanggung jawab menerjemahkan dan melaksanakan kebijakan pendidikan untuk membentuk watak dan akhlak siswa, dalam hal ini meminimalkan kenakalan remaja. Penelitian ini bertujuan untuk menganalisis implementasi kebijakan pendidikan dalam mengatasi kenakalan remaja. Penelitian ini menggunakan metode kualitatif dengan jenis penelitian deskriptif dengan pendekatan studi dokumen/teks. Hasil penelitian menunjukkan bahwa dalam mewujudkan keberhasilan implementasi kebijakan pendidikan untuk mengatasi kenakalan remaja, ada tiga hal yang dapat dipengaruhi: logika yang digunakan oleh suatu kebijakan, sifat kerjasama yang dibutuhkan, dan sumber daya manusia yang cukup besar. Selain itu, dalam penjabaran pelaksanaannya akan berhasil jika juga memperhatikan komunikasi, sumber daya, sikap warga sekolah, dan struktur birokrasi yang berlaku.Kata kunci: Kebijakan Pendidikan, Siswa, Kenakalan Remaja.